Agile Processes in Software Engineering and Extreme Programming: 22nd International Conference on Agile Software Development, XP 2021, Virtual Event, June 14-18, 2021, Proceedings - Gregory, Peggy; Lassenius, Casper; Wang, Xiaofeng; Kruchten, Philippe (Lecture Notes in Business Information Processing, 2021)
This open access book constitutes the proceedings of the 22nd International Conference on Agile Software Development, XP 2021, which was held virtually during June 14-18, 2021. XP is the premier agile software development conference combining research and practice. It is a unique forum where agile researchers, practitioners, thought leaders, coaches, and trainers get together to present and discuss their most recent innovations, research results, experiences, concerns, challenges, and trends.  XP conferences provide an informal environment to learn and trigger discussions and welcome both people new to agile and seasoned agile practitioners. This year’s conference was held with the theme “Agile Turns Twenty While the World Goes Online”. The 11 full and 2 short papers presented in this volume were carefully reviewed and selected from 38 submissions. They were organized in topical sections named: agile practices; process assessment; large-scale agile; and short contributions.